Complex Approach to Evaluating Quality of Medical Care in Pediatrics - A. A. Baranov (Pediatričeskaâ Farmakologiâ, 2015)
The article is dedicated to evaluating quality of medical care of children. Improvement of this parameter and public health indicators is the key goal of a healthcare system of any country at the moment. The authors analyzed different systems of evaluating quality of medical care of children and demonstrated their benefits and drawbacks. The article presents a complex algorithm of evaluating quality of medical care developed by the authors; it involves structural, procedural and effective components of this term and corresponds with a complex model of simultaneous control organization on the professional level as well as on the regulatory level with due regard to the degree of specialist/patient interaction.